PENGEMBANGAN ALAT PRAKTIKUM VISKOMETER METODE BOLA JATUH BEBAS BERBASIS SENSOR EFEK HALL UGN3503 SEBAGAI MEDIA PEMBELAJARAN FISIKA - Diajeng Ramadhan; Vina Serevina; Raihanati Raihanati (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
This research aims to develop learning media in the form of practical tool viscometer to measure the viscosity of the fluid using the method ball free fall to utilize hall effect sensor UGN3503 as detection sensor iron ball as it passes through the fluid and causes the magnetic field of the sensor is changed because the sensor is blocked by a magnetic iron ball, the magnitude magnetic field strength by a hall effect sensor changed into electrical quantities such as voltage output. The voltage generated is to be processed and recorded as the travel time by the microcontroller Atmega8. The method used is the method of Research and Development with the model design using ADDIE (Analyze, Design, Develop, Implement, Evaluate). The steps in the development of practical tools viscometer is analysis, the initial product design, develop products, revisions and enhancements, implementation and evaluation. Retrieval of data validation using instruments such as questionnaires to matter experts, media experts and teachers. Viscosity value is determined by measuring the travel time of the ball, the density of ball and fluid, and the distance of the ball. The results of field trials small scale with research subjects 5 high school students (100%) it was concluded that the development practical tool viscometer method ball free fall based hall effect sensor UGN3503 on type of fluid glycerin and oil SAE 40 can be used as a medium of learning physics so as to facilitate students in understanding the concept of viscosity. Keywords: development, lab instruments, viscometer